From Welfare State To Identity Formation: Islamic Education Governance in the World's Three Largest Muslim Nations - Raikhan Raikhan (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2026)
Islamic education in the three countries with the world's largest Muslim populations Indonesia, Pakistan, and India demonstrates the complexity of religious institutional adaptation to distinct state frameworks. The shift in the global demographic center of the Muslim population from the Middle East to Asia necessitates a comparative understanding of how Islamic education systems respond to the challenges of modernization, curriculum reform, and the demands for social mobility. This study aims to analyze the structures and regulatory frameworks of Islamic education, identify the challenges of curriculum reform, and explore the function of Islamic education as a vehicle for identity formation and social mobility across these three nations. The research employs a qualitative approach utilizing a cross-national case study design. Data were collected through policy document analysis (Indonesian Ministerial Regulation KMA 1503/2025, Pakistan's Single National Curriculum, India's National Education Policy 2020), government reports, and peer-reviewed literature published between 2019 and 2026. Data were analyzed using comparative thematic analysis, incorporating source triangulation to ensure credibility. The study identifies three models of Islamic education: the integrative-moderate model (Indonesia), characterized by the full integration of madrasahs into the national system and high social mobility; the ideological-parallel model (Pakistan), where madrasahs function as de facto welfare providers despite 86% of graduates entering the informal sector ; and the defensive-independent model (India), which is shifting toward national standardization through controversial policies. Resistance to curriculum reform in Pakistan and India is driven by ideological and political factors, whereas Indonesia employs a collaborative approach. Consequently, there is no monolithic model of Islamic education; rather, systemic success is measured by adaptability to 21st-century challenges without compromising Islamic ethics. Indonesia serves as a best practice for integration, whereas Pakistan and India face structural challenges necessitating context-specific approaches.